Benzonitrile Insertion into Silylarylamides – ansa‐Bis(benzamidinate) Ligand Systems with Rigid o‐ and m‐Phenylene Linkers in the Synthesis of Lithium and Rare Earth Complexes. Issue 24 (1st July 2013) - Skvortsov, Grigorii G.; Fukin, Georgy K.; Ketkov, Sergey Yu.; Cherkasov, Anton V.; Lyssenko, Konstantin A.; Trifonov, Alexander A.
Abstract: The reactions of the lithium silylarylamides [1, 2‐C6 H4 (NSiMe3 )2 Li2 ]2 and [1, 3‐C6 H4 (NSiMe3 )2 Li2 ] with two equivalents of PhCN [tetrahydrofuran (thf), room temp.] is an efficient synthetic approach to the ansa ‐bis(amidinate) ligand systems [1, 2‐C6 H4 {NC(Ph)NSiMe3 }2 Li2 (thf)]2 and [1, 3‐C6 H4 {NC(Ph)NSiMe3 }2 Li2 (thf)2 ]2, which were isolated in 54 and 60 % yields, respectively. However, lithium silylarylamide [2, 6‐C5 H3 N(NSiMe3 )2 Li2 ] containing a pyridine fragment does not undergo PhCN insertion even at elevated temperatures (thf, toluene), and the reaction affords the silylarylamido complex [2, 6‐C5 H3 N{NSiMe3 }2 Li2 ]3 · (C6 H5 CN)4, which contains a coordinated benzonitrile molecule. The different reactivity of the compounds correlates with the changes in the molecular orbital energies estimated by DFT calculations. The salt metathesis reaction of anhydrous YCl3 with lithium amidinate [1, 2‐C6 H4 {NC(Ph)NSiMe3 }2 Li2 (thf)]2 in 2:1 molar ratio (thf, 20 °C) afforded a neutral bis(amidinate) chloro yttrium complex [1, 2‐C6 H4 {NC(Ph)NSiMe3 }2 ]YCl(thf)2 in 80 % yield. With NdCl3, the analogous reaction resulted in a trinuclear neodymium chloro ate complex with a rather unusual μ‐bridging lateral coordination of the amidinate fragment [1, 2‐C6 H4 {NC(Ph)NSiMe3 }2 Nd(thf)(μ‐Cl)(1, 2‐C6 H4 {NC(Ph)NSiMe3 }2 Nd{μ‐Cl}2 )][Li(thf)2 ]. Abstract : The synthesis of ansa ‐bis(amidinate) ligand systems with rigid o ‐phenylene, m ‐phenylene, and 2, 6‐pyridine linkers is described. Surprisingly, in the reaction of lithium silylarylamide containing a 2, 6‐disubstituted pyridyl linker, no amidinate formation occurs and a lithium amido complex containing benzonitrile coordinated to Li forms.